2020
DOI: 10.3390/cancers12082049
|View full text |Cite
|
Sign up to set email alerts
|

TP53 Mutation Analysis in Gastric Cancer and Clinical Outcomes of Patients with Metastatic Disease Treated with Ramucirumab/Paclitaxel or Standard Chemotherapy

Abstract: Loss of p53 promotes vascular endothelial growth factor (VEGF)-A up-regulation and the angiogenic potential of cancer cells. We investigated TP53 somatic mutations in 110 primary gastric adenocarcinomas of two retrospective metastatic series including 48 patients treated with second-line Ramucirumab/Paclitaxel and 62 patients who received first-line chemotherapy with Cisplatin or Oxaliplatin plus 5-Fluorouracil. Missense mutations were classified by tumor protein p53 (TP53) mutant-specific residual transcripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 34 publications
(71 reference statements)
1
7
0
Order By: Relevance
“…aggressiveness. TP53 was found to be the most commonly mutated gene, in line with previous reports on TP53 mutations detected in up to two-thirds of metastatic GEC patients [28].…”
Section: Discussionsupporting
confidence: 90%
“…aggressiveness. TP53 was found to be the most commonly mutated gene, in line with previous reports on TP53 mutations detected in up to two-thirds of metastatic GEC patients [28].…”
Section: Discussionsupporting
confidence: 90%
“…The mutation rate of the tumor suppressor gene TP53 is 46% in GC. Deletion of TP53 may upregulate vascular endothelial growth factor A (VEGF-A) expression and promote cancer cell angiogenesis, leading to a poor prognosis ( 36 ). Gurzu et al ( 37 ) analyzed a large number of human gastric cancer samples and found that mutation of exon 7 in TP53 may induce downregulation of the expression of the tumor suppressor gene Maspin, which leads to GC invasion and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…To improve the diagnosis rate, we further analyze the abnormally expressed genes in patients with aggressive pituitary adenomas from the perspective of genetics. It has been found that the expression of Ki67, P53, and VEGF is significantly increased in malignant tumors such as gastric cancer, bladder cancer renal cell carcinoma, and glioma (19)(20)(21)(22). We speculate they are also abnormally expressed in aggressive pituitary adenomas.…”
Section: Discussionmentioning
confidence: 75%